Heritable strategies for controlling insect vectors of disease - Burt, Austin (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2014)
Mosquito-borne diseases are causing a substantial burden of mortality, morbidity and economic loss in many parts of the world, despite current control efforts, and new complementary approaches to controlling these diseases are needed. One promising class of new interventions under development involves the heritable modification of the mosquito by insertion of novel genes into the nucleus or of Wolbachia endosymbionts into the cytoplasm. Once released into a target population, these modifications can act to reduce one or more components of the mosquito population's vectorial capacity (e.g. the number of female mosquitoes, their longevity or their ability to support development and transmission of the pathogen). Some of the modifications under development are designed to be self-limiting, in that they will tend to disappear over time in the absence of recurrent releases (and hence are similar to the sterile insect technique, SIT), whereas other modifications are designed to be self-sustaining, spreading through populations even after releases stop (and hence are similar to traditional biological control). Several successful field trials have now been performed with Aedes mosquitoes, and such trials are helping to define the appropriate developmental pathway for this new class of intervention.